Dedicated versus mainstreaming approaches in local climate plans in Europe. (September 2019) - Reckien, D.; Salvia, M.; Pietrapertosa, F.; Simoes, S.G.; Olazabal, M.; De Gregorio Hurtado, S.; Geneletti, D.; Krkoška Lorencová, E.; D'Alonzo, V.; Krook-Riekkola, A.; Fokaides, P.A.; Ioannou, B.I.; et al.
Abstract: Cities are gaining prominence committing to respond to the threat of climate change, e.g., by developing local climate plans or strategies. However, little is known regarding the approaches and processes of plan development and implementation, or the success and effectiveness of proposed measures. Mainstreaming is regarded as one approach associated with (implementation) success, but the extent of integration of local climate policies and plans in ongoing sectoral and/or development planning is unclear. This paper analyses 885 cities across the 28 European countries to create a first reference baseline on the degree of climate mainstreaming in local climate plans. This will help to compare the benefits of mainstreaming versus dedicated climate plans, looking at policy effectiveness and ultimately delivery of much needed climate change efforts at the city level. All core cities of the European Urban Audit sample were analyzed, and their local climate plans classified as dedicated or mainstreamed in other local policy initiatives. It was found that the degree of mainstreaming is low for mitigation (9% of reviewed cities; 12% of the identified plans) and somewhat higher for adaptation (10% of cities; 29% of plans). In particular horizontal mainstreaming is a major effort for local authorities; an effort that does not necessarily pay off in terms of success of action implementation. This study concludes that climate change issues in local municipalities are best tackled by either, developing a dedicated local climate plan in parallel to a mainstreamed plan or by subsequently developing first the dedicated and later a mainstreaming plan (joint or subsequent "dual track approach"). Cities that currently provide dedicated local climate plans (66% of cities for mitigation; 26% of cities for adaptation) may follow-up with a mainstreaming approach. This promises effective implementation of tangible climate actions as well as subsequent diffusion of climate issues into other local sector policies. The development of only broad sustainability or resilience strategies is seen as critical. Highlights: Trends in mainstreaming climate change issues were analyzed for 885 cities EU-28. EU cities provide numerous local mitigation (#664) and/or adaptation (#321) plans. Mainstreaming was investigated as vertical and horizontal approach. 9% of cities have mainstreamed mitigation LCP; 12% of mitigation LCPs mainstreamed. 10% of cities have mainstreamed adaptation LCP; 29% of adaptation LCPs mainstreamed.